2020
DOI: 10.1186/s12887-020-02388-z
|View full text |Cite
|
Sign up to set email alerts
|

Looking into the life of technology-dependent children and their caregivers in Korea: lifting the burden of too many responsibilities

Abstract: Background The number of technology-dependent children (TDC) is increasing in South Korea, but available healthcare services after their discharge are poor. This study aimed to examine how TDC and caregivers live at home and identify their difficulties and needs regarding home care with few services to support them. Methods This cross-sectional study was conducted in a tertiary hospital for children in South Korea. A self-reported questionnaire was completed by primary caregivers of TDC who were younger than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Given this level of heterogeneity, it is not surprising that families raising these children face issues that are multifaceted. A large body of research over a considerable time frame and in multiple contexts demonstrates the impact on parents, and the frequency of unmet parental support needs (Choi et al, 2020;Shudy et al, 2006). Increasing attention has been paid to the specific burdens parents experience, such as financial and social hardships (Thomson et al, 2016), the time demands (McCann et al, 2012) and sleep disturbance (Angelhoff et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Given this level of heterogeneity, it is not surprising that families raising these children face issues that are multifaceted. A large body of research over a considerable time frame and in multiple contexts demonstrates the impact on parents, and the frequency of unmet parental support needs (Choi et al, 2020;Shudy et al, 2006). Increasing attention has been paid to the specific burdens parents experience, such as financial and social hardships (Thomson et al, 2016), the time demands (McCann et al, 2012) and sleep disturbance (Angelhoff et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The number of children (0-19 years old) requiring technology-dependent, specific home-based healthcare techniques, such as tracheal suctioning, tracheostomy, and percutaneous endoscopic gastrostomy, has doubled from 8,438 in 2007 to 19,712 in 2017 in Japan despite vast improvements in the survival rates of premature infants (Ministry of Health, Labour and Welfare, 2020). An analogous trend was also observed internationally (Breneol et al, 2019;Choi et al, 2020). The demand for registered community nurses is increasing to provide technical advice to family caregivers in addition to the employment of hygienic, accurate, and comfortable healthcare techniques (Nageswaran et al, 2017;Sobotka et al, 2019;Choi et al, 2020;Colley et al, 2020a;Whalen et al, 2020).…”
Section: Introductionmentioning
confidence: 70%
“…An analogous trend was also observed internationally (Breneol et al, 2019;Choi et al, 2020). The demand for registered community nurses is increasing to provide technical advice to family caregivers in addition to the employment of hygienic, accurate, and comfortable healthcare techniques (Nageswaran et al, 2017;Sobotka et al, 2019;Choi et al, 2020;Colley et al, 2020a;Whalen et al, 2020).…”
Section: Introductionmentioning
confidence: 70%
“…A survey reported that caregivers of medical technology-dependent children in Korea had substantial problems taking care of their sick children and managing medical devices at home. 22 Studies have urged the establishment of a well-equipped environment and a partnership between hospitals and community care systems for successful tracheostomy management after discharge. 23 24 To provide proper care after discharge, a referral system and home healthcare services must be developed throughout the country.…”
Section: Discussionmentioning
confidence: 99%